Enhancing protection against vector-borne diseases in forcibly displaced communities: evaluating the efficacy of spatial repellents for cutaneous leishmaniasis control in North-East Syria - Richard Allan; Ramona Scherrer; Ozge Erisoz Kasap; Laura Paris; Thomas Scott; Hendrik Sauskojus; Olivia Wetherill; Sara Estecha-Querol; Zaid Alkhalaf; Mehmet Karakus; Ayda Yilmaz; Bülent Alten; et al. (BMC Medicine)
Abstract Background In Syria, during the 14 years after the outbreak of civil war, 16.7 million people have been forced to flee their homes, of which 7.2 million remain internally displaced in 2025. Breakdown in waste management caused by aerial bombardment has created ideal conditions for cutaneous leishmaniasis (CL) transmission, vectored by phlebotomine sandflies. Displaced populations reside in flimsy shelters where conventional vector control tools are operationally unfeasible. A small, lightweight, portable transfluthrin-based spatial repellent (Mosquito Shield™) has been developed which may circumvent some of these logistical issues and provide improved protection from vector-borne diseases in harsh environments. Methods A two-arm, non-randomised cluster trial was undertaken in Ar-Raqqa governorate, North-East Syria, to evaluate the efficacy of Mosquito Shield™ in reducing CL case incidence and sandfly densities in shelters. Weekly epidemiological monitoring was performed by MENTOR Initiative mobile clinics and supported health facilities. Entomological monitoring was performed fortnightly using indoor US Centers for Disease Control and Prevention light traps in 40 randomly selected households per study arm. Phlebotomine sandflies were morphologically identified; a subset were analysed for molecular species confirmation, blood-meal preferences and pyrethroid resistance. Household surveys and focus group discussions were used to assess intervention feasibility, acceptability and uptake. Results Assuming a 2-month diagnosis cut-off, the CL incidence rate was 9.9 and 5.2 per 1000 in the control and intervention arms, respectively; Mosquito Shield™ demonstrated a significant impact on rate of CL infection in all ages (incidence rate ratio; IRR: 0.52 [95% CI: 0.37–0.74]; p < 0.0001). Mosquito Shield™ demonstrated a significant impact on all female sandfly density (IRR: 0.22 [95% CI: 0.14–0.33]; p < 0.0001) and blood-fed female sandfly density (IRR: 0.21 [95% CI: 0.11–0.40]; p < 0.0001). Mosquito Shield™ was received positively and perceived to be easy to use, to protect from CL, sandflies and other insect bites and required minimal behaviour change. Conclusions Trial findings provide the first demonstrable impact of spatial repellents on CL transmission, strengthening the growing evidence basis for the effectiveness of this intervention against multiple vector species and their associated pathogens. Study results strongly support the deployment of spatial repellents to control CL in humanitarian crises. Trial registration ClinicalTrials.gov, NCT06917040.